IJCM_194A: Diabetes distress and associated factors among adult patients residing in an urban resettlement colony in Delhi - Alwani Anam Anil; Kaur Ravneet; Bairwa Mohan; Misra Puneet; Nongkynrih Baridalyne (Wolters Kluwer Medknow Publications, 2024)
Background: Diabetes distress "refers to the negative emotional or affective experiences resulting from the challenge of living with the demands of diabetes." The American Diabetes Association recommends routinely screening for distress. Presently, this does not take place and distress remains undiagnosed. Objectives: This study aimed to determine the prevalence of diabetes distress, its associated factors and the relationship between glycemic control and distress. Methodology: This community-based, cross-sectional study was conducted in a resettlement colony in Delhi. The participants were selected using simple random sampling and included adults diagnosed with DM. The sample size calculated was 433 (prevalence: 42%, absolute precision: 5%, non-response rate: 10%). The questionnaire included Diabetes Distress Scale 17 and Diabetes Self-Management Questionnaire. Fasting blood sugar (FBS) was tested for all the participants. Logistic regression was used to determine the factors associated with distress as well as the association between glycemic control status and the presence of distress. Results: 412 adults were included in the study, of which 35.4% had clinically significant distress. The factors found to be associated with diabetes distress on multivariable logistic regression were: female sex, belonging to the lower socio-economic status, having self-reported comorbidities, being diagnosed with diabetes 10 or more years ago, being on treatment from a private or government hospital as compared to not being on treatment and having an unmet need for social support. There was a positive association between physician contact and distress. Those with poor glycemic control had higher odds of distress, regimen related distress and emotional burden, as compared to those who had adequate glycemic control. Conclusion: In this study, distress was prevalent among 35.4% of adults with diabetes. The factors determined to be associated with distress may provide a targeted approach to address distress, which ought to be screened for in routine clinical settings and be addressed, to help improve disease control.